Impact of technology evolution on the materialised views: current issues and future trends. (16th April 2019) - Sebaa, Abderrazak; Nouicer, Amina; Tari, Abdelkamel
To improve query performance materialised views were largely used for such purpose. So far, this technique has been a success as testified by the large and increasing interest among industrial and research communities in the use of this technique. In this paper, we investigate the related issues of materialised views and the most important solutions and framework of the literature review. Then, we explore the information technology impact on the evolution of materialised view applications, related environments and data models. Finally, we summarise the opportunities and future challenges caused by combination and trends of such evolution.